Analisis Value At Risk Portofolio Saham Menggunakan Metode Varian-Kovarian - Nur Rizki Wahidah; Yuki Novia Nasution; Nanda Arista Rizki (EKSPONENSIAL, 2018)
Investing is a human effort to save a certain amount of money in time, in the hope of gaining some profit in the future. Investment decisions are fundamentally related to the management of funds in a given period, in which investors have hope to earn income or profit from the funds invested. Almost all investors do not want losses when investing. Various ways are done to avoid loss, or at least maximize profits with minimal risk. The value of risk that is often used is Value At Risk (VaR). Values ​​At Risk (VaR) is one of the statistical tools used to measure the maximum loss of an asset or investment over a certain period with a certain degree of confidence to reduce the occurrence of the risk. This study aims to determine how the risk of stock portfolio of PT. Astra Agro Lestari Tbk (AALI) and PT.PP London Sumatra Indonesia Tbk (LSIP) use Value at Risk analysis using Varian-Covariance method at closing price of shares incorporated in Jakarta Islamic Index (JII) and Asset Value at Risk PT. Astra Agro Lestari Tbk (AALI) and PT.PP London Sumatra Indonesia Tbk (LSIP) to Value at Risk Portfolio. The results showed that if the initial fund invested to PT. Astra Agro Lestari Tbk. and PT.PP London Sumatra Indah Tbk. Rp. 10.000.000, - with a 95% confidence level obtained Value at Risk (VaR) of Rp. 369.682. this can be interpreted there is a 95% confidence that the losses received by investors will not exceed from Rp. 369.682..The result of PT. Astra Agro Lestari tbk. against portfolio risk at 6% and PT. PP London Sumatra Indonesia Tbk. of portfolio risk is 46%.